Pengaruh Asimetri Informasi, Ukuran Perusahaan, dan Employee Stock Ownership Program pada Praktik Manajemen Laba - Dewi, Anak Agung Istri Sarasmitha; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
This study aims to obtain empirical proves the effect of information asymmetry, firm size, employee stock ownership program on earnings management practices. Information symmetry is measured using relative bid-ask spreads, firm size is measured using ln (total assets), and employee stock ownership program with the proportion of shares disbursed by the company for employees. This research was conducted on companies listed on the Stock Exchange that adopted ESOP in 2014 until 2016. The theory underlying this research is agency theory. The sampling method used in this study was purposive sampling. The sample of companies in the study were 14 companies with 42 observations. Data collection uses non-participant observation methods. The data analysis technique used is multiple linear regression analysis. Keywords: Information asymmetry, earnings management